Mutans Streptococci Count and Salivary Histatin 5 Level in Relation to Early Childhood Caries (Medico Legal Update, 2021)
Background: ECC is one of the most common chronic infectious diseases of preschool-aged children (3).Mutans Streptococci (MS) is the cheif microorganism that causes ECC Saliva is a significant factor in thedevelopment of teeth decay. Saliva have many innate defense molecules that take part in the protection oforal tissues by either direct antimicrobial effect or interference with microbial colonization. These moleculesinclude antimicrobial peptides AMPs among the main natural antimicrobial proteins of saliva . Salivaryhistatine-5 (HST-5) is one of the protective factors in saliva that possess anti-bacterial properties againstseveral types of oral bacter. This study aimed to measure the viable count of mutans streptococci and salivaryhistatin 5 level in relation to early childhood caries.Materials and Method: Sixty three children with ages of 4-5 years old were enrolled in this study. Theywere divided into two groups; 33 children with severe type of ECC) ategory as the study group and 30 cariesfree child) as the control group. Unstimulated saliva sample were collected for ms count on mitis bacitracinagar and for evaluation of salivary Histatin 5 level.Results: Statistical analysis revealed that M.S. count was higher significantly in study group compared tothan control group and salivary histatin 5 was significantly higher than the control group.